2006
DOI: 10.1038/sj.bmt.1705484
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary complications after T-cell-depleted allogeneic stem cell transplantation: low incidence and strong association with acute graft-versus-host disease

Abstract: Lung injury limits the success of allogeneic stem cell transplantation (SCT). The overall incidence varies from 30 to 50% and non-infectious causes occur in one-third to one-half of these. We reviewed pulmonary complications in 369 consecutive patients who received a partially T-celldepleted myeloablative allogeneic hematopoietic SCT at our institution between 1993 and 2003. All patients were treated uniformly with cyclophosphamide followed by total body irradiation. Control subjects were matched on sex, under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In a study of HCT recipients with bloodstream infections, postengraftment events were associated with worse outcomes, including death (62). "Late onset" noninfectious PCs, which may be subjected to diagnostic inaccuracy (63), have been associated with acute and chronic GVHD (35,64,65) and mortality (66). Many subjects in our study had multiple PCs, suggesting susceptibility to recurrent lung injury, incomplete resolution, and/or misdiagnosis and treatment of a previous PC.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of HCT recipients with bloodstream infections, postengraftment events were associated with worse outcomes, including death (62). "Late onset" noninfectious PCs, which may be subjected to diagnostic inaccuracy (63), have been associated with acute and chronic GVHD (35,64,65) and mortality (66). Many subjects in our study had multiple PCs, suggesting susceptibility to recurrent lung injury, incomplete resolution, and/or misdiagnosis and treatment of a previous PC.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Although most of the patients are reported to have multiple related risk factors, it is indicated that pulmonary complications do not develop in this entire high-risk group of patients that suggest that pathogenesis and the risk factors have not been completely understood yet. 5 The aim of this study was to evaluate the risk factors of FPIs due to HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all of the previous studies were limited to case reports or series that did not include more than 10 cases of COP/BOOP, and/ or did not analyze COP/BOOP independently but rather as a part of late-onset non-infectious pulmonary complications. 6,7,[10][11][12][14][15][16][17] To the best of our knowledge, only one report, from Seattle, has included more than 20 cases (49 cases with COP/BOOP). 8 Thus, we performed a large retrospective study that included about 200 patients with COP/BOOP.…”
Section: Introductionmentioning
confidence: 99%